PENGARUH LATIHAN FOOTWORK TERHADAP KELINCAHAN PADA ATLET PUTRA PERSATUAN BULUTANGKIS MANDIRI PEKANBARU U-15 - Angga Kurnia Putra; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research was conducted to determine whether there are effects of exercise on the footwork for agility the badmintonplayers to get maximum result when playing badminton. The problem encountered when the observation is the latest athlete to reach or return the punch. This assumption is lack of footwork’s agility in the mastery of the field then when returning the punch was not optimal. The purpose of this research is to look at the effects of exercise on the footwork for agility in men athlete of Persatuan Bulutangkis Mandiri Pekanbaru U-15. This research is a form of research with experimental treatment (Experimental), with a population of men athlete of Persatuan Bulutangkis Mandiri Pekanbaru U-15, in this research all population sample of 5 people. The instruments used in this research is agility court test, which aims to measure the agility. Afterthat, data is processed with statistics, to the test normality of the test at significant level 0,05α lilifors. Hypothesis proposed, exercise effect of footwork to agility. Based on t test analysis produces 15,10 Thitung and 2,015 Ttabel, its means Thitung>Ttabel. Based on analysis of statistical data, there are on Pree-test average was 13,40 and post-test average was 12,26, data is normal. Then Ha go through, there is a Exercise Effect of Footwork  for agility in men athlete of Persatuan Bulutangkis Mandiri Pekanbaru U-15. Key Words: Footwork, Agility, Badminton